Joint symbol detection and channel estimation for MIMO-OFDM systems via the variational Bayes EM algorithm - Zhang, Xiao-Ying; Wei, Ji-Bo; Wang, De-Gang; Xiong, Chun-Lin (Tongxin Xuebao, 2010)
A new joint symbol detection and channel estimation algorithm was proposed for MIMO-OFDM systems over the time-varying fading channel based on the variational Bayes expectation maximization algorithm and Turbo principle. The channel estimation error covariance matrix was considered in the soft-input soft-output detector which circumvented the undesirable exhaustive search via list sphere decoder (LSD). In addition, a novel Kalman forward-backward channel estimator was derived based on the posterior distributions of the transmitted symbols which were obtained from the space-time detection. Simulation results show that the proposed algorithm has more robust performance than the conventional EM algorithm and decision-directed technique in the time varying multipath channel.